Penurunan waktu proses cleaning in place (CIP) dengan cara wet wash pada produksi susu bubuk di PT XYZ: Reduce cleaning in place (CIP) wet wash process time in powdered milk production at PT XYZ - Dwimarlina, Anggun; Setya Budi Muhammad Abduh; Al-Baari, Ahmad Ni’matullah (TEKNOLOGI PANGAN : Media Informasi dan Komunikasi Ilmiah Teknologi Pertanian, 2023)
The diversity of products in a company makes the process of cleaning production areas important to prevent cross contamination. Cleaning in Place (CIP) is a method to clean product residues from production equipment automatically without the need to disassemble the machine. This study aims to determine the required minimum time for the CIP drying process to dry the production equipment. The experiment was done by testing the treatment based on changes in compressed air, drying, and cooling process time. Cleaning verification was done by examining visual inspection and test for detection of microbial contamination, allergens and ATP. The results showed that reducing the CIP processing time can be done by minimizing the drying time. The best treatment resulted in the treatment with compressed air 300 s, drying 900 s and cooling 900 s. This can be seen from the 3 repetitions, the results obtained by examining the overall appearance of the surface in the tote bin are clean and dry. In addition, changes in the time parameter did not affect the cleaning process of residues on the surface of the tote bin, which was shown in the results of testing for detection of microbial contamination, allergens and ATP.